Synthesis and biological evaluation of thiazole derivatives as LbSOD inhibitors - Camila C. Bitencourt Brito; Hélder Vinicius Carneiro da Silva; Daci José Brondani; Antonio Rodolfo de Faria; Rafael Matos Ximenes; Ivanildo Mangueira da Silva; Julianna F. C. de Albuquerque; Marcelo Santos Castilho (Taylor & Francis Group, 2019)
Leishmaniasis is considered as one of the major neglected tropical diseases due to its magnitude and wide geographic distribution. Leishmania braziliensis, responsible for cutaneous leishmaniasis, is the most prevalent species in Brazil. Superoxide dismutase (SOD) belongs to the antioxidant pathway of the parasites and human host. Despite the differences between SOD of Leishmania braziliensis and human make this enzyme a promising target for drug development efforts. No medicinal chemistry effort has been made to identify LbSOD inhibitors. Herein, we show that thermal shift assays (TSA) and fluorescent protein-labeled assays (FPLA) can be employed as primary and secondary screens to achieve this goal. Moreover, we show that thiazole derivatives bind to LbSOD with micromolar affinity.